Human resource development challenges and solutions in Vietnam’s state-owned joint stock companies - Tran, Hung Van; Tran, Anh Viet; Vo, Lien Thi Ngoc (International Journal of Management and Sustainability, 2023)
The relationship between employee job satisfaction and the challenges faced by state-owned joint-stock companies can be intricate and multifaceted. The goal of this study is to look into the level of job satisfaction that employees report as well as the challenges that state-owned joint-stock companies in Vietnam face when developing their human resources. As part of this study, the researchers collected and reviewed the replies of 186 former employees of the parent company. Descriptive statistics such as frequencies, percentages, and mean averages were used. Overall, employees at Saigon Water Supply Corporation, a one- limited liability company, expressed a moderate level of satisfaction with the management policies of the company. The annual growth in the number of training programs for staff members coincides with an increase in the quality of the evaluation results for both training and the development of human resources, which have demonstrated an upward trend from 2019 to 2021. It is essential for both individuals and organizations to have a solid foundation upon which to build a successful future. The cultivation of human resources is one of the most important factors in the establishment of this foundation in state-owned joint-stock corporations.